1998
DOI: 10.1111/j.1365-2621.1998.tb15746.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Extracellular Ice Nucleator Effects on Freezing of Foods

Abstract: Extracellular ice nucleators (ECINs) were incorporated into foods and subjected to subzero freezing. Time-temperature profiles, ice-formation patterns and textures were examined by thermocouple, microscopy and texture analyzer. Onset temperatures (initial freezing), enthalpies and freezing rates were measured by DSC. Addition of ECINs to liquid foods elevated ice nucleation temperatures and promoted freezing. Solid or semisolid products frozen with ECINs resulted in a fiber-like texture. These effects were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…As to the effect of cooling temperature, similar results had been obtained by Li and Lee (1998). In their experiments 10 mL water samples were frozen at À6, À12 and À18°C.…”
Section: Peptonesupporting
confidence: 73%
See 1 more Smart Citation
“…As to the effect of cooling temperature, similar results had been obtained by Li and Lee (1998). In their experiments 10 mL water samples were frozen at À6, À12 and À18°C.…”
Section: Peptonesupporting
confidence: 73%
“…Ryder and Lee studied the freezing of fish muscle with a dispersion of P. syringae at a concentration of 10 7 colony-forming units per mL (CFU/mL) (Li and Lee, 1998). The treated groups were sprayed with about 0.1 mL of the dispersion per gram of fish muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Fixation of structure the morphological characteristics and ice formation patterns in frozen foods 113,114 and have shown potential in freeze drying, cryopreservation, and freeze concentration. These substances are present in several biological organisms such as bacteria, fungi, insects, and even frogs 115 ; however, recent studies and technological applications have focused on microbial INAs.…”
Section: Phase Separation By Freezingmentioning
confidence: 99%
“…Researches on the freezing of solutions in the presence of INAB have revealed that INAB can not only increase ice-nucleation temperature but also affect the ice formation pattern and food texture (Hwang, Coetzer, Tumer, & Lee, 2001;Li & Lee, 1998). The microstructure of solids is totally different from that of solutions.…”
Section: Ice Crystal Sizementioning
confidence: 99%
“…Li and Lee (1998) have found that the incorporation of extracellular ice nucleators (ECINs) from Erwinia herbicola into liquid model food, including sugar solutions, protein solutions, and oil/water suspensions, led to elevated ice-nucleation temperature, reduced freezing time and the formation of fiber-like textures. Watanabe and Arai (1994) have studied the effects of the addition of INAB on the freeze concentration of fresh foods such as fresh milk, fresh lemon juice, and raw egg white and found that the texture, flavor and color of foods were improved by the addition of INAB.…”
Section: Introductionmentioning
confidence: 99%